Efektivitas Antibakteri Ekstrak Daun Jengkol (Pithecellobium jiringa) terhadap Pertumbuhan Salmonella typhimurium: Studi In Vitro Menggunakan Metode Difusi Cakram - Rahayu, Kun Mardiwati; Chairani, Anastasia (Biocaster : Jurnal Kajian Biologi, 2025)
Salmonella typhimurium bacterial infection remains one of the main causes of gastrointestinal diseases, and cases of resistance to conventional antibiotics are increasing. This encourages the search for alternative therapies based on natural ingredients, one of which is jengkol leaves (Pithecellobium jiringa) which are known to contain antibacterial compounds. This study is an in vitro experimental study aimed at evaluating the antibacterial effectiveness of ethyl acetate extract of jengkol leaves (Pithecellobium jiringa) against the growth of Salmonella typhimurium using the Kirby-Bauer disc diffusion method. Four extract concentrations (10%, 20%, 40%, and 80%) were tested against bacterial suspensions with chloramphenicol as a positive control, and DMSO as a negative control. Data were analyzed using one-way ANOVA and continued with Duncan's test to determine significant differences between treatments. The results showed a significant increase in the diameter of the inhibition zone as the extract concentration increased with the highest effectiveness at a concentration of 80% (mean inhibition zone 16.07 mm; strong category). Analysis shows that active compounds, such as flavonoids, tannins, and saponins, work through cell wall damage and bacterial membrane permeability. These findings indicate that jengkol leaf extract has potential as a natural antibacterial agent against gram-negative bacteria such as Salmonella typhimurium and is worthy of further development in phytopharmaceutical-based infection control efforts.